Customer Behavior on Purchasing Channels of Sustainable Customized Garment With Perceived Value and Product Involvement - Li, Zhenfang; Yuan, Jia; Du, Bisheng; Hu, Junhao; Yuan, Wenwen; Palladini, Lorenzo; Yu, Bing; Zhou, Yan (Frontiers in Psychology, 2020)
Online shopping for customized garments has become the fastest-growing field of the Chinese eBusiness market. Obviously most consumers not only limit to buy standardized garments but also want to buy customized garments with their preferences. This phenomenon pushed up the fashion textile and apparel industry to change their supply chain operations to fulfill the customized demand. Besides, the fashion textile and apparel industry also want to study how different channel factors will affect consumers' perceived value and further influence consumers' purchasing decisions. We initiated this study and empirically tested more than 200 experienced consumers. This study collaborated with a fashion textile and apparel company who aims to implement customized product lines soon. Based on the perceived value theory and risk management theory, we investigated that the product involvement and channel identification on supply chain design will affects potential customized product consumers' purchasing decisions. The findings reveal that channels' recognition has affects consumers' decisions with positive impacts on their perceived value. And also consumers' the perceived risk and shopping channel involvement has a negative impact on their perceived values and channel selections. In addition, product involvement has a moderating effect to the relationship between channel's perceived risk, perceived values and channel selections as well.